Supervisi dan Peranannya pada Sekolah Dasar - Nahdatul Hazmi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the role of supervision in developing the quality of teachers in teaching. This research is a qualitative research with the subject of the school principal and teacher. The results showed that the principal in leading was unable to enforce rules and discipline to all teachers, only following the decisions of their members. When there is a learning process and teaching devices that are lacking there is no sanction or reprimand from the school principal, teaching at this school only follows each other's rules. But when there is inspection from the supervisor or UPT there is new communication between the teacher. The existence of an unexpected meeting resulted in disruption of the teaching and learning process, because the teacher's meeting made the students did not supervise, so the students wandered. Conclusion, in the end the learning process that has been arranged well in the learning device is not carried out properly, because the teacher who teaches will pursue the hours of study used during a sudden meeting, as a result students will find it difficult to understand the lessons given by the teacher. Keywords: Supervision, Role of School Principals